Modelling microbial inactivation kinetics under time-varying temperature conditions - Gil, M. M. (2004)
The Gompertz model was applied for describing inactivation, assuming a typical pasteurisation temperature profile at food surface. In order to test the regression analysis procedure parameters were estimated on the basis of pseudo-experimental data. Results were compared to the ones obtained assuming processes at constant temperature. Care should be taken, if parameters estimated under isothermal conditions are going to be used for predicting inactivation under dynamic conditions.